Kontribusi SDM Bidang Ekonomi Kreatif Dalam Mengurangi Kemiskinan - Sinaga, Nailan Ni’mah; Leli, Nur; Pasaribu, Yogi Oriena (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The creative industry is an important field that must continue to be developed over time and needs to be built together in its development because it is one of the pillars of the country’s economy. This research aims to find out that the creative economy plays an important role in improving the Indonesian economy to increase employment opportunities and reduce poverty. Literature study was chosen as the method. The development of the creative economy shows a positive picture because the economic growth generated is above average. The main factor that drives the growth of the creative industry in Indonesia is the quality of human resources which continues to develop and is dominated by young people plus the ability of human resources who can combine culture with art.